Kekecewaan terhadap Peran Orang Tua sebagai Sumber Ide Penciptaan Karya Seni Rupa Instalasi - Kamilah, Dini; Hadi Prayitno, Eko (Program Studi Pendidikan Seni Rupa FBS UNJ, 2024)
This work aims to raise awareness about gender equality issues within the family, especially between parents, so that gender equality education can be provided to their children. The research uses a qualitative method with an artistic research approach. The creation concept are reflective art interests, figurative forms, and contemporary aesthetic principles. This interactive installation uses assemblage techniques. Artwork 1 incorporates a frame, watercolor montage, and magnets with specific symbols, depicting the failure of gender equality implementation in the family. Artwork 2 features watercolor paintings printed on umbrellas as the primary medium, illustrating the successful implementation of gender equality in the family.